Insights into copper sensing and tolerance in Pneumocystis species - Porollo, Aleksey; Sayson, Steven G.; Ashbaugh, Alan; Rebholz, Sandra; Landero Figueroa, Julio A.; Cushion, Melanie T. (Frontiers in Microbiology, 2024)
Pneumocystis species are pathogenic fungi known to cause pneumonia in immunocompromised mammals. They are obligate to their host, replicate extracellularly in lung alveoli and thrive in the copper-enriched environment of mammalian lungs. In this study, we investigated the proteome of Pneumocystis murina, a model organism that infects mice, in the context of its copper sensing and tolerance. The query for copper-associated annotations in FungiDB followed by a manual curation identified only 21 genes in P. murina, significantly fewer compared to other clinically relevant fungal pathogens or phylogenetically similar free-living fungi. We then employed instrumental analyses, including Size-Exclusion Chromatography Inductively Coupled Plasma Mass Spectrometry (SEC-ICP-MS), Immobilized Metal Affinity Chromatography (IMAC), and Liquid Chromatography-Tandem Mass Spectrometry (LC-MS/MS), to isolate and identify copper-binding proteins from freshly extracted organisms, revealing 29 distinct cuproproteins. The RNA sequencing (RNA-seq) analysis of P. murina exposed to various CuSO4 concentrations at three temporal intervals (0.5, 2, and 5 hours) indicated that significant gene expression changes occurred only under the highest CuSO4 concentration probed (100 µM) and the longest exposure duration (5 hours). This stimulus led to the upregulation of 43 genes and downregulation of 27 genes compared to untreated controls. Quantitative PCR (qPCR) confirmed the expression of four out of eight selected upregulated genes, including two assumed transcription factors (PNEG_01236, PNEG_01675, and PNEG_01730) and a putative copper transporter (PNEG_02609). Notably, the three applied methodologieshomology-based annotation, SEC-ICP-MS/IMAC/LC-MS/MS, and RNA-seqyielded largely distinct findings, with only four genes (PNEG_02587, PNEG_03319, PNEG_02584, and PNEG_02989) identified by both instrumental methods. The insights contribute to the broader knowledge of Pneumocystis copper homeostasis and provide novel facets of host-pathogen interactions for extracellular pathogens. We suggest that future studies of Pneumocystis pathogenicity and copper stress survival should consider the entire spectrum of identified genes.